The role and regulatory mechanisms of the TCA cycle in early embryonic development - Lai, Yipan; Gao, Xiurong; Zhao, Liwen; Liu, Jin; Gao, Chao; Yan, Qingfu; Zeng, Yangneng; Liao, Zibing; Zhong, Jianing (Frontiers in Cell and Developmental Biology, 2025)
The tricarboxylic acid cycle (TCA cycle) serves as a critical metabolic hub in embryonic development. Its dynamic reprogramming not only coordinates energy supply and biosynthesis but also profoundly influences cell fate decisions through the metabolic-epigenetic coupling mechanism. This review systematically explores the TCA cycle central role in driving the adaptive metabolic changes of embryos, such as mitochondrial maturation and lineage differentiation, and precisely regulating the timing of zygotic genome activation (ZGA). It highlights how the nuclear translocation of key enzymes in the TCA cycle creates a nuclear metabolic microenvironment, which directly regulates histone modifications (acetylation, methylation) and DNA demethylation through intermediate products like Ac-CoA and α-ketoglutarate (α-KG), thereby achieving epigenetic remodeling. Additionally, the review emphasizes the pathological mechanisms by which mitochondrial dysfunction (such as insufficient ATP synthesis, abnormal metabolite accumulation, and oxidative stress imbalance) leads to developmental arrest through epigenetic disorders and DNA damage.